Лемківське весілля - Гайова Є. (Народна творчість та етнографія, 2008)
This article is based on the field ethnographic material. The author collected this material during the scientific expeditions to Lemkiv villages of Velyka Bereznyanka region in Transcarpathian oblast in 2002 - 2005 . Basic stages of the rite are presented in the article: the rites which take place before wedding, svatanky (matchmaking), ohlyadyny or obzory (bride show), marriage ceremony, the rite of covering the head of the bride with chepets (houve) and a shawl.